2021
DOI: 10.12688/f1000research.51912.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to under-reporting of patient safety incidents in Indonesia: leaders’ perspectives

Abstract: Background: Understanding the causes of patient safety incidents is essential for improving patient safety; therefore, reporting and analysis of these incidents is a key imperative. Despite its implemention more than 15 years ago, the institutionalization of incident reporting in Indonesian hospitals is far from satisfactory. The aim of this study was to analyze the factors responsible for under-reporting of patient safety incidents in Indonesian public hospitals from the perspectives of leaders of hospitals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…First, Indonesian hospitals may not give incident reports priority because there was no timeline in submitting the report to the external agency, because delays in completing the incident reports were identified as common problem in Indonesian hospitals. 30 Second, there might be a delay in analyzing the incident at the national level because the incident reported may be several months old, thus also delaying feedback from national level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Indonesian hospitals may not give incident reports priority because there was no timeline in submitting the report to the external agency, because delays in completing the incident reports were identified as common problem in Indonesian hospitals. 30 Second, there might be a delay in analyzing the incident at the national level because the incident reported may be several months old, thus also delaying feedback from national level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also revealed the absence of external incident reporting timeline did not have a specified deadline that resulted in delay of reporting incident at the national level. 30…”
Section: Classification Of Incident Reportedmentioning
confidence: 99%
“…Patient safety incidents in Indonesia remain high (Larasati and Dhamanti, 2021). Although there are 2,877 accredited hospitals in Indonesia, the incidence of patient safety incidents is still 12 %, totaling 7,465 reports (Dhamanti et al, 2021). This figure comprises 38% near-missed events (NMEs), 31% no-harm events (NHEs), and 31% adverse events (AEs) (Tuck et al, 2014;Wau and Purba, 2019;Toyo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%